2011
DOI: 10.4081/mr.2011.e12
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori in periodontal pockets of chronic periodontitis patients with and without type II diabetes mellitus: a randomized controlled trial

Abstract: This randomized controlled study evaluated the association of Helicobacter pylori (H. pylori) with chronic periodontitis patients with and without type II Diabetes Mellitus. H. pylori is considered to be a pathogen responsible for gastritis, peptic ulcers and a risk factor for gastric cancer. The aim of the present study was to evaluate the association of H. pylori with chronic periodontitis patients with and without type II diabetes mellitus before and after treatment. The prevalence of H. pylori in periodont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…1 Though Helicobacter pylori (H. pylori) have been considered as a main cause of mucosa associated lymphoma, peptic ulcer disease, type B gastritis, and gastric adenocarcinoma, roles of foods and especially dairy products in its transmission are still unknown. [2][3][4] H. pylori was found in stomach of domestic animals in the absence of associated gastritis, it was recovery from milk, meat and gastric tissue of domestic ruminants suggest that domestic animals and their milk may be reservoirs of H. pylori. [2][3][4] Suitable circumstances for growth and survival of H. pylori in milk and dairy products provide adequate settings for transmission of H. pylori from these foodstuffs to human.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Though Helicobacter pylori (H. pylori) have been considered as a main cause of mucosa associated lymphoma, peptic ulcer disease, type B gastritis, and gastric adenocarcinoma, roles of foods and especially dairy products in its transmission are still unknown. [2][3][4] H. pylori was found in stomach of domestic animals in the absence of associated gastritis, it was recovery from milk, meat and gastric tissue of domestic ruminants suggest that domestic animals and their milk may be reservoirs of H. pylori. [2][3][4] Suitable circumstances for growth and survival of H. pylori in milk and dairy products provide adequate settings for transmission of H. pylori from these foodstuffs to human.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] H. pylori was found in stomach of domestic animals in the absence of associated gastritis, it was recovery from milk, meat and gastric tissue of domestic ruminants suggest that domestic animals and their milk may be reservoirs of H. pylori. [2][3][4] Suitable circumstances for growth and survival of H. pylori in milk and dairy products provide adequate settings for transmission of H. pylori from these foodstuffs to human. 5 The severity of clinical complications caused by H. pylori is depends on several factors.…”
Section: Introductionmentioning
confidence: 99%
“…24 In contrast, Berroteranand co-workers found no relationship between HP infection and periodontal disease (Loe and Sillness indices), dental caries, and dental hygiene. 25 In this research,it was specified that periodontal diseases and DMFT indexhad meaningful relationship with gastric HP infection.Some studies have declared that shift in oral flora and systemic inflammation can affect some organs such as stomach, and pancreas 28 and result in tumor development and growth. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Over the years several researchers have pondered on and studied the association between periodontal disease and Hp infection. They obtained positive results on the presence of the bacterium in the oral cavity and above all on the association of the two diseases suggesting that the oral cavity acts as an extra-gastric reservoir [10]. Furthermore, Gürbüz et al [7] reported a positive association between levels of dental plaque and the levels of gastric and oral Hp.…”
Section: Association Between Oral Hygiene/periodontal State and Helicmentioning
confidence: 98%